Production planning and control : a comprehensive approach - Kiran, D. R. (Butterworth-Heinemann, 2019)
Production Planning and Control draws on practitioner experiences on the shop floor, covering everything a manufacturing or industrial engineer needs to know on the topic. It provides basic knowledge on production functions that are essential for the effective use of PP & C techniques and tools. It is written in an approachable style, thus making it ideal for readers with limited knowledge of production planning. Comprehensive coverage includes quality management, lean management, factory planning, and how they relate to PP & C. End of chapter questions help readers ensure they have grasped the most important concepts. With its focus on actionable knowledge and broad coverage of essential reference material, this is the ideal PP & C resource to accompany work, research or study. Uses practical examples from the industry to clearly illustrate the concepts presentedProvides a basic overview of statistics to accompany the introduction to forecastingCovers the relevance of PP & C to key emerging themes in manufacturing technology, including the Industrial Internet of Things and Industry4.